2024
DOI: 10.1002/ccd.30953
|View full text |Cite
|
Sign up to set email alerts
|

The BALTO Registry: Long‐term results of percutaneous BALloon pericardioTomy in oncological patients

Borja Rivero‐Santana,
Santiago Jimenez‐Valero,
Alfonso Jurado‐Roman
et al.

Abstract: ObjectivesThe aim of this study was to analyze the efficacy and safety of percutaneous balloon pericardiotomy (PBP) in oncological patients who present with a malignant pericardial effusion (MPE).BackgroundThe use of PBP as a treatment for MPE is not standardized due to the limited evidence. Furthermore, the performance of a second PBP for a recurrence after a first procedure is controversial.MethodsThe BALTO Registry (BALloon pericardioTomy in Oncological patients) is a prospective, single‐center, observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…During this current period of low PBP use, one group has persisted in using it to treat malignant effusion, particularly with evidence of tamponade, and has reported their results in the BALTO registry with 76 PBP procedures over a 15-year span. 2 The authors demonstrated the procedure's safety and efficacy, with relief of effusion/tamponade in all patients and only two serious nonfatal complications. However, the recurrence rate of pericardial effusion or tamponade was relatively high at 24.5%, occurring early at a median of 2.4 months; in this subgroup, PBP could be performed successfully a second time in all cases.…”
mentioning
confidence: 86%
“…During this current period of low PBP use, one group has persisted in using it to treat malignant effusion, particularly with evidence of tamponade, and has reported their results in the BALTO registry with 76 PBP procedures over a 15-year span. 2 The authors demonstrated the procedure's safety and efficacy, with relief of effusion/tamponade in all patients and only two serious nonfatal complications. However, the recurrence rate of pericardial effusion or tamponade was relatively high at 24.5%, occurring early at a median of 2.4 months; in this subgroup, PBP could be performed successfully a second time in all cases.…”
mentioning
confidence: 86%